Aditivos alimentares em dietas com alta concentração de amido para ovinos - Vilaça, Lucas Eduardo Gonçalves (2025)
The inclusion of additives in the diet of ruminants improves feed conversion, stimulates dry matter intake and promotes weight gain, in addition to bringing benefits to ruminal health and the immune system. The objective was to evaluate the total apparent digestibility, blood biochemistry, dry matter intake and nutrients according to the experimental diets proposed for ½ Dorper and ½ Santa Inês sheep, containing amylolytic enzymes, live yeast and tannin. We used 5 ½ Dorper and ½ Santa Inês sheep, females with an average age of 6 months. The animals were randomly divided into individual metabolic cages equipped with a trough, drinker and salt shaker according to the INCT standard, using a Latin square design (5x5), considering 5 treatments and 5 experimental periods. The experiment was divided into five phases, with each phase lasting 10 days for adaptation to each experimental diet to be tested and 5 days for digestibility collections to evaluate leftovers, food and water consumption, fecal and urinary production every day. At the same time, on days 1, 3 and 5, blood was collected to evaluate metabolites, and on the 5th day, blood was collected to evaluate glycemia. Totaling a total of 75 days of experiment. The experimental diets were: 1 – Control (without additives); 2 – Amylolytic Enzyme + Tannin (TE); 3 – Amylolytic Enzyme + Live Yeast (EL); 4 – Live Yeast + Tannin (TL); 5 – Live Yeast + Tannin + Amylolytic Enzyme (TLE). The experimental diets will be formulated and balanced according to the NRC (2007), containing a forage:concentrate ratio of 25:75. The CP digestibility parameters and the water intake/DM ratio showed statistical differences between treatments. For the other data on nutrient intake and digestibility, water intake, and urinary and fecal production, the different additive combinations did not promote significant changes to the animals. Similarly, the additives did not cause deleterious changes to the blood metabolites of the animals in this study. Therefore, it can be stated that the use of different combinations of feed additives for sheep does not cause undesirable changes to the animals. For the performance experiment, we allocated 25 animals, 10 males and 15 females with an average age of approximately 60 days of life. The diets tested will be the same as those used in the digestibility study (Control, TE, TL, EL, and TLE). For performance, we evaluated dry matter and nutrient intake and biometric measurements: front and rear height, body length, chest width and thoracic and barrel circumference, weight and body condition score (BCS) every 30 days, during 90 days of confinement. For intake and biometric data in relation to treatment, the different combinations of additives did not promote significant changes in the animals, however, in relation to the period, all data were significant. Therefore, it can be stated that the use of different combinations of feed additives for sheep does not cause undesirable changes in the animals.